1989
DOI: 10.1128/jb.171.3.1428-1434.1989
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of beta-chlorinated four-carbon aliphatic acids

Abstract: Alcaligenes sp. strain CC1 is able to grow on several a-chlorinated aliphatic acids (2-chlorobutyrate, 2-chloropropionate, and chloroacetate), as wel as on the n-chlorinated four-carbon aliphatic acids trans-3-chlorocrotonate, cis-3-chlorocrotonate, and 3-chlorobutyrate as sole carbon and energy sources. Dehalogenation of a-chlorinated acids could be measured by using resting cells grown on all the different carbon sources, whereas dehalogenation of P-chlorinated four-carbon acids could be detected only by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…CMPA is further catabolized by a pathway similar to that proposed for other chlorinated aliphatic acids. Kohler-Staub and Kohler (1989) demonstrated that the dechlorination (and hence degradation) of trans-3-chlo- rocrotonic acid and 3-chlorobutyric acid required that both the molecules underwent prior conversion to the corresponding CoA derivatives. We found the dehalogenation of CMPA to be CoA-dependent and the reaction involved appeared not to be stereospecific.…”
Section: Discussionmentioning
confidence: 99%
“…CMPA is further catabolized by a pathway similar to that proposed for other chlorinated aliphatic acids. Kohler-Staub and Kohler (1989) demonstrated that the dechlorination (and hence degradation) of trans-3-chlo- rocrotonic acid and 3-chlorobutyric acid required that both the molecules underwent prior conversion to the corresponding CoA derivatives. We found the dehalogenation of CMPA to be CoA-dependent and the reaction involved appeared not to be stereospecific.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Pseudomonas putida [28] 'Coryneform' [29] Pseudomonas cepacia [30] Ah'aligenes sp. CC1 [31 ] pounds that do support growth are expected to have evolved such that their activity with these synthetic molecules is increased. Biochemical recalcitrance thus is a problem of enzyme specificity and activity.…”
Section: 2-dichloroethanementioning
confidence: 99%
“…CC1 [31 ] pounds that do support growth are expected to have evolved such that their activity with these synthetic molecules is increased. Biochemical recalcitrance thus is a problem of enzyme specificity and activity.…”
Section: -Chlorocrotonatementioning
confidence: 99%
“…Kohler-Staub and Kohler [31] have characterized an Alcaligenes sp., strain CC1, that grows with 3-chlorocrotonic and 3-chlorobutyric acid as sole carbon and energy source. Dechlorination of these fourcarbon acids occurs after activation of the acids …”
Section: Dehalogenation During ~-Oxidationmentioning
confidence: 99%